Ca2+ induced Lipid Peroxidation Accentuates Aging in Rat Brain Mitochondria - Mohan Kumar B. S.; Mahaboob Basha P. (Journal of Stress Physiology & Biochemistry, 2025)
Aging in rats is multifactorial and include decline in biological, physiological, psychological and social changes. The antioxidant imbalance is one of the commonest factors during aging and age-related diseases. Several studies have identified the participation of various antioxidant’s differential activity levels in the brain. However, Ca2+ is known to alter the homeostatic balance of these antioxidants. Lipid peroxidation is the chief marker of membrane architecture disruption in the aging and neurodegenerative diseases. In the current study, we have focused on the contribution of Ca2+ participation, its concentration and effect on the lipid peroxidation at various stages of rat’s life. We have observed that LPO induction is increased in mitochondria isolated from aged rats in comparison to young adult and neonatal rats. Treatment of 100 to 300uM Ca2+ has shown a steady increase in lipid peroxidation of up to 20% in mitochondria isolated from aged rats while neonates and young rats have displayed differential levels of peroxidation from 17% to 15%. Thus, alleviating role of Ca2+ in lipid peroxidation in aging and neurodegeneration.